GENOTOXICITY OF SHALLOW WATERS NEAR THE BRAZILIAN ANTARCTIC STATION "COMANDANTE FERRAZ" (EACF), ADMIRALTY BAY, KING GEORGE ISLAND, ANTARCTICA - Arthur José da Silva Rocha (10476330); Marina Tenório Botelho (10476393); Fabio Matsu Hasue (10476336); Maria José de Arruda Campos Rocha Passos (10476327); Caroline Patricio Vignardi (10476396); Phan Van Ngan (10476339); Vicente Gomes (6854393) (2015)
Series of biomonitoring surveys were undertaken weekly in February 2012 to investigate the genotoxicity of the shallow waters around the Brazilian Antarctic Station "Comandante Ferraz" (EACF). The comet assay was applied to assess the damage to the DNA of hemocytes of the crustacean amphipods Gondogeneia antarctica collected from shallow waters near the Fuel Tanks (FT) and Sewage Treatment Outflow (STO) of the research station, and compare it to the DNA damage of animals from Punta Plaza (PPL) and Yellow Point (YP), natural sites far from the EACF defined as experimental controls. The damage to the DNA of hemocytes of G. antarctica was not significantly different between sites in the biomonitoring surveys I and II. In survey III, the damage to the DNA of animals captured in shallow waters near the Fuel Tanks (FT) and Sewage Treatment Outflow (STO) was significantly higher than that of the control site of Punta Plaza (PPL). In biomonitoring survey IV, a significant difference was detected only between the FT and PPL sites. Results demonstrated that the shallow waters in front of the station may be genotoxic and that the comet assay and hemocytes of G. antarctica are useful tools for assessing genotoxicity in biomonitoring studies of Antarctic marine coastal habitats.